2021
DOI: 10.3389/fpsyg.2021.697550
|View full text |Cite
|
Sign up to set email alerts
|

Research at a Distance: Replicating Semantic Differentiation Effects Using Remote Data Collection With Children Participants

Abstract: Remote data collection procedures can strengthen developmental science by addressing current limitations to in-person data collection and helping recruit more diverse and larger samples of participants. Thus, remote data collection opens an opportunity for more equitable and more replicable developmental science. However, it remains an open question whether remote data collection procedures with children participants produce results comparable to those obtained using in-person data collection. This knowledge i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…For example, multiple studies explained that providing hotspots was particularly effective in reducing barriers to participation, especially for racially or ethnically diverse and low-income populations [ 5 , 6 , 14 , 26 ]. Other studies that did not provide hotspots cited a lack of internet as an exclusion factor as well as a study limitation [ 11 , 15 , 21 , 23 , 24 , 28 ]. Studies that excluded participants without access to the internet limited the generalizability of their study population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, multiple studies explained that providing hotspots was particularly effective in reducing barriers to participation, especially for racially or ethnically diverse and low-income populations [ 5 , 6 , 14 , 26 ]. Other studies that did not provide hotspots cited a lack of internet as an exclusion factor as well as a study limitation [ 11 , 15 , 21 , 23 , 24 , 28 ]. Studies that excluded participants without access to the internet limited the generalizability of their study population.…”
Section: Discussionmentioning
confidence: 99%
“…Method section). What is more, a growing number of research in developmental psychology started to evaluate the validity of online testing, and demonstrated that online studies yielded similar results as in-person studies (e.g., Rhodes et al, 2020; Schidelko et al, 2021; Vales et al, 2021; Yamamoto et al, 2021). In particular, Rhodes et al (2020) conducted online several studies that were originally face-to-face, with paradigms similar to the one presented here, and with children of the same age range (between 4 and 8 years old).…”
Section: Discussionmentioning
confidence: 99%
“…However, researchers may often want to prevent unwanted parental involvement (e.g., additional unmonitored explanations, biasing of responses) or require children to input their own responses, especially if accurate response times are needed. As children learn to communicate independently, they may be less likely to need parental intervention, with research suggesting children as young as 4 years of age can independently input their responses during remote research (Vales et al, 2021). To limit parental involvement during data collection, researchers can read instructions to children or use pre-recorded audio or videos (Rhodes et al, 2020).…”
Section: Task Considerations and Instructionsmentioning
confidence: 99%